Urgensi E-Bisnis dan Pencatatan Laporan Keuangan UMKM pada Era Digital di Desa Jatimekar - Sukmayadi Sukmayadi; Ading Rahman Sukmara (CV. Ulil Albab Corp, 2024)
In the digital era, the role of e-business and financial report management has crucial relevance for the growth of MSMEs. This research explores the impact of implementing e-business and education on recording financial reports on MSMEs in Desa Jatimekar. The results show a marked increase in understanding among MSMEs regarding the benefits of e- business and the potential use of digital technology. Identification of MSME sectors, such as local crafts and agricultural products, as potential for adopting e-business provides a strategic basis for further development. Although enthusiasm for e-business implementation is high, challenges such as limited access to technology and uncertainty about data security remain a concern. The use of financial reports is also faced with challenges of complexity and integration with basic daily needs. Recommendations include providing additional technical support and stakeholder involvement in information security to ensure the sustainability and security of e-business implementation and financial recording in Desa Jatimekar. This study provides insight into the importance of MSME adaptation to digital trends at the village level, contributing to understanding and policy development in this area.